MENGINTEGRASIKAN TEKNOLOGI INFORMASI DAN KOMUNIKASI (TIK) DALAM PENDIDIKAN BAHASA INGGRIS UNTUK MENINGKATKAN EFEKTIVITAS PENGAJARAN DAN PEMBELAJARAN DALAM PROGRAM PENDIDIKAN FARMASI - Yulia Oktafia Jasman; Ledya Fitriyana; Ade Suhendra; Widya Syafitri; Zulfani Sesmiarni (Universitas Mahaputra Muhammad Yamin, 2026)
The rapid globalization and digital transformation of healthcare require pharmacists to master professional communication and digital literacy alongside pharmacological expertise. Therefore, English for Specific Purposes (ESP), particularly English for Pharmacy (EfP), must integrate Information and Communication Technology (ICT) to reflect authentic professional practices. This study aims to systematically examine how ICT is applied, perceived, and evaluated in EfP instruction within pharmacy education. This Systematic Literature Review (SLR) analyzed 22 peer-reviewed articles published between 2014 and 2024, retrieved from Scopus, Web of Science, and ERIC, using keywords related to ICT, ESP, English for Pharmacy, and pharmacy education. Articles were selected based on predefined inclusion and exclusion criteria and analyzed thematically. The review reveals three key findings. First, ICT integration in EfP has evolved from basic digital content delivery to student-centered models such as the Flipped Classroom, which consistently enhances learning outcomes and student satisfaction. Second, Mobile Learning is the most widely adopted technology, particularly effective in improving vocabulary mastery and professional communication skills. Third, successful ICT adoption is strongly influenced by UTAUT factors and supported by blended learning approaches, while major challenges include limited infrastructure, insufficient faculty training, and constraints on personalized feedback. This study contributes to ESP and pharmacy education by providing an evidence-based framework for strategic ICT integration in EfP, offering pedagogical guidance for educators and directions for future research, including the potential use of Artificial Intelligence in professional language instruction.